Clinical-epidemiological profile and outcome of old people hospitalized for COVID-19 - Soares, Ticianne da Cunha; Gomes, Aline Tavares; Machado, Ana Larissa Gomes; Matos Neto, Emídio Marques de; Aguiar, Bruno Guedes Alcoforado; Madeira, Maria Zélia de Araujo (Revista de Enfermagem da UFPI, 2023)
Objective: to describe the clinical-epidemiological profile and outcome of old people hospitalized for COVID-19 at the University Hospital of Piauí. Methods: An observational, cross-sectional study was carried out with secondary data involving 137 medical records of old patients hospitalized for COVID-19 in the UH during the period from April to December 2020. Data were collected in August and September 2021. A form consisting of questions equivalent to the sociodemographic and epidemiological data of old patients was used. Data were analyzed using SPSS statistical software version 25. Results: It was observed that the "use of mechanical ventilation" (Odds Ratio: 35.96 [10.23-126.47]) and "type of hospitalization bed" (Odds Ratio: 9.40 [2.69-32.82]) were the variables that best explain the deaths being independent predictors for this outcome. There was a statistically significant association between the number of comorbidities (p=0.007), the presence of clinical manifestations (p=0.003), the number of clinical manifestations (p=0.003) and death. The shorter survival time was associated with ICU admission and use of mechanical ventilation (p=0.000). Conclusion: The results of the study show that the presence of risk factors for COVID-19, clinical manifestations of the disease, to be admitted to ICU beds, using MV and those who were older had worse outcomes.